Property owner’s attitude towards assessment tax obligation / Shamsinar Rahman, Fadilah Puteh and Nurma Abdul Manap - Rahman, Shamsinar; Puteh, Fadilah; Abdul Manap, Nurma (Universiti Teknologi MARA Cawangan Pahang, 2021)
Tax is an important source of income to the government. Assessment tax or property tax is one of the main income to the local government in Malaysia. The successful collection of the assessment tax will ensure smooth and efficient implementation of local government administration. The taxpayer’s attitude towards assessment tax obligation has been identified as one of the factors that contribute towards assessment tax arrears. The objective of this study is to provide extensive reviews of the property owner’s attitude towards their assessment tax obligations. The extensive review is hoped to provide deeper understanding on the issue of assessment tax arrears as well as contribute to the body of knowledge in tax and local government context.